PENGARUH PENGERASAN MATA GERGAJI DAN POLA PENGGERGAJIAN TERHADAP KARAKTERISTIK PENGGERGAJIAN KAYU KARET - Osly Rachman (Jurnal Penelitian Hasil Hutan, 1989)
This  article presents   study   result  on sawing  characteristics   of  rubberwood   (Havea  brasiliensis  Muell.  Arg.) subjected to  different cutting  edge  hardness  and  sawing pattern.   The  material   used  in study   comprised   40  logs with  length  1.30   m and  diameter   ranging from   13.  75 to  26.00   cm.  Half  of  these  logs were sawn with  full stellite  cutting  edge and live sawing pattern.  The  rest  were  sawn  with  alternate  stellite   tiped  cutting   edge and  half  sawing pattern.   The parameters   studied  in sawing  process   consisted   of  power   consumption,    feeding   rate,  recovery,  productivity     and  the  relationship   between   log diameter  and log taper with  recovery.The  result  of  statistical  analysis  shows  that  sawblade   with  alternate  stellite  tiped  consums  less power  compared  with full  stellite   tiped,  Meanwhile  cutting   edge  hardness  has no significant   effect  on feeding  rate. The result also indicates  that  live sawing  and  half sawing pattern   yield  recovery  as  much  as 35.9%   and  40.9%   respectively   which  was significantly   dif- ferent  each others.  Finally,  sawing productivity    is not significantly   affected   by sawing pattern   applied.